1993
DOI: 10.1175/1520-0426(1993)010<0591:taovos>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Voluntary Observing Ships' Meteorological Observations-Results of the VSOP-NA

Abstract: For the Voluntary Observing Ships Special Observing Project for the North Atlantic (VSOP-NA), the layout, meteorological instrumentation, and observing practices of 45 voluntary observing ships (VOS) operating in the North Atlantic were cataloged. Over a two-year period these ships provided extra information with each observation, and the effect of different observing practices has been quantified by using analysis fields from an atmospheric forecast model as a comparison standard. Biases of order several tent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 4 publications
2
109
1
Order By: Relevance
“…The decrease in the day − night difference in U EL since the early 1980s supports this idea. The larger day − night difference in U EL during the 1960s to early 1980s, of about 0.3 ms −1 , could be explained if observers were underestimating the sea state, and hence the wind speed, at night (Kent et al, 1993). The day − night difference (order 0.1 ms −1 or less) shown by U M10 is more likely to be correct, which suggests that the much larger day − night difference in the visually estimated observations is spurious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the day − night difference in U EL since the early 1980s supports this idea. The larger day − night difference in U EL during the 1960s to early 1980s, of about 0.3 ms −1 , could be explained if observers were underestimating the sea state, and hence the wind speed, at night (Kent et al, 1993). The day − night difference (order 0.1 ms −1 or less) shown by U M10 is more likely to be correct, which suggests that the much larger day − night difference in the visually estimated observations is spurious.…”
Section: Discussionmentioning
confidence: 99%
“…Kent et al (1993) showed that reports from ships' estimated winds were biased low at night, but the tendency for a low bias was reduced for those ships carrying an anemometer. We found very little day − nighttime bias in measured ship winds.…”
Section: Discussionmentioning
confidence: 99%
“…Visual estimates of wind speed are harder to make at night (e.g. Kent et al, 1993) and we therefore also analysed night and daytime data separately (Table IV). The data showed a tendency for the daytime wind speed distribution to be slightly stronger than the night-time, although overall the differences are small.…”
Section: Effect Of Adjustments For Known Inhomogeneitiesmentioning
confidence: 99%
“…Ship heading with respect to the prevailing winds and waves may also affect the visual estimate of wind (Thomas and Swail, 2004). Such factors, and others, such as possible variations in the Beaufort scale with time and recruiting country (Lindau, 1995b) and the influence of anemometers on ships reporting U E (Kent et al, 1993), also require further investigation.…”
Section: Possible Sources Of Residual Inhomogeneitymentioning
confidence: 99%
See 1 more Smart Citation